Konsep Transportasi Trem di Smart City Makassar - Saskia Pratiwi; Muh. Yamin Jinca; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
The rapid growth of the population in Makassar causes various problems, one of which is congestion. Congestion occurs because of the imbalance in the growth of road geometric conditions with the volume of existing vehicles. Mass transportation is one solution to congestion problems. Rail-based public transportation mode is an effective mode of transportation for carrying large numbers of passengers. One mode of rail-based mass transportation is the tram. This study aims to determine the ideal tram transportation system, the potential for the application of trams in Makassar and recommend the concept of tram transportation for Makassar. The analytical method used is descriptive qualitative analysis, synthesis of literature studies, comparative analysis and spatial analysis. Based on the results of the analysis of aspects 1) of the economy, 2) social and 3) the environment, the potential for the implementation of tram technology in Makassar City is very large. Recommendations for applying tram transportation in Makassar City include vehicle recommendations, route recommendations and station recommendations and stops.